THE EFFECT OF MOTIVATION ON EMPLOYEE PERFORMANCE AT THE REGIONAL REVENUE AGENCY OFFICE MAJENE REGENCY - Hartawati, Sri Indira (Jurnal Ekonomi Balance, 2019)
Motivation will encourage the emergence of sharp competition between individuals, groups, society and society at the organizational level to between countries. Motivation can be seen as a change of energy in a person that is characterized by the feeling and preceded by a response to the purpose. Every motivation given by an organization must have a different impact. One of the impacts that occur is the impact on the performance of employees or employees. The government must understand the motivation given to each employee to maintain and increase employee loyalty. This study uses qualitative and quantitative data using several population techniques and samples. The research was conducted at the office of the revenue agency of the Majene district. The results of the Motivation study did not have a significant effect on Employee Performance in the Regional Revenue Agency of Majene Regency.